Simultaneous transarterial chemoembolization and radiofrequency ablation for large hepatocellular carcinoma - Duan, Feng (World J Gastrointest Oncol, 2020)
BACKGROUND: Hepatocellular carcinoma (HCC) is a common cancer and a leading cause of tumor-related death. Patients with large HCC (≥ 8 cm) are at an advanced stage and have poor prognosis, and hepatic resection may not be suitable, and the incidence of postoperative recurrence is high. AIM: To evaluate recurrence and mid-term survival of patients with large HCC treated by transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA). METHODS: This was a retrospective study. From 2010 to 2013, 46 consecutive patients with large HCC were treated with simultaneous TACE and RFA. Thirty-five of 46 patients had a single tumor. Progression-free survival (PFS) and overall survival (OS) were analyzed at 2 years and 3 years, respectively. RESULTS: Forty-six patients treated by simultaneous TACE and RFA had no significant complications and treatment was successful. After 3 years, median PFS and OS were 10.21 ± 1.58 mo and 26.44 ± 2.26 mo, retrospectively. The survival rate was 67.5% after 2 years and 55.67% after 3 years. CONCLUSION: These preliminary data show that simultaneous TACE and RFA are safe and effective for large HCC.